Implementation of coronary computed tomography angiography as nationally recommended first-line test in patients with suspected chronic coronary syndrome: impact on the use of invasive coronary angiography and revascularization. (5th September 2020) - Nissen, Louise; Winther, Simon; Schmidt, Morten; Rønnow Sand, Niels Peter; Urbonaviciene, Grazina; Zelechowski, Marek Wojciech; Christensen, Martin Kirk; Busk, Martin; Lambrechtsen, Jess; Diederichsen, Axel; Elpert, Frank-Peter; Grove, Erik Lerkevang; et al.
Abstract: Aims : To investigate the impact of applying coronary computed tomography angiography (CCTA), as the recommended first-line diagnostic test in patients with suspected chronic coronary syndrome (CCS) on the use of invasive coronary angiography (ICA) and revascularization practice. Methods and results : We included all patients undergoing a first-time CCTA ( n  = 53555) and first-time ICA ( n  = 41451) from 2008 to 2017 due to suspected CCS in Western Denmark (3.3 million inhabitants). The number of CCTA procedures increased from 352 (2008) to 7739 (2017) (2098%), ICA examinations declined from 4538 to 3766 (17%). The average proportion of no- or non-obstructive coronary artery disease by CCTA was 77.5%. Referral to ICA after CCTA occurred in 16.9% of patients in 2008–10 vs. 13.9% in 2014–17 ( P  < 0.0001). Revascularization in patients referred to ICA after CCTA increased from 33.8% in 2008–10 vs. 44.4% in 2014–17 ( P  < 0.0001). The revascularization proportion in patients undergoing ICA with no preceding CCTA was 32.3% in 2008–10 vs. 33.3% in (2014–17) ( P  = 0.1063). Stratified by age, the overall revascularization proportion increased in the younger age groups and was unchanged or decreased in older age groups: <50 years: 60% increase, 50–59 years: 33% increase, 60–69 years: 0%, and >70 years: 9.5% decrease. Conclusion : The introduction of CCTA as a first-line diagnostic test in patients with suspected CCS does not associate with increased use of invasive angiography and seems to have facilitated a more appropriate revascularization practice.